2020
DOI: 10.1155/2020/1231807
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Pathogenic Potential, Virulent Genes Profile, and Antibiotic Susceptibility of Proteus mirabilis from Urinary Tract Infection

Abstract: Proteus mirabilis is the third most common bacterium that can cause complicated UTI, especially in catheterized patients. Urovirulence genes of P. mirabilis strains are poorly identified among UTI patients. e aims of the present study were to determine the prevalence of the uropathogenic P. mirabilis strains isolated from UTI patients by the detection of several P. mirabilis virulence genes and to characterize the antibiotic susceptibility profile of P. mirabilis isolates. P. mirabilis isolates were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 19 publications
(28 reference statements)
9
14
0
Order By: Relevance
“…hpmA , which is encoded by CriePir89, is mainly responsible for tissue damage [ 35 ]. Finally, rpoA gene associated with urovirulence and antibiotic efficiency [ 36 ] was revealed in this strain.…”
Section: Resultsmentioning
confidence: 99%
“…hpmA , which is encoded by CriePir89, is mainly responsible for tissue damage [ 35 ]. Finally, rpoA gene associated with urovirulence and antibiotic efficiency [ 36 ] was revealed in this strain.…”
Section: Resultsmentioning
confidence: 99%
“…The rsb A gene expresses a membrane sensor that induces the production of extracellular polysaccharides. Also, it regulates the swarming phenomena and enhances the biofilm formation by P. mirabilis 23 , 50 , 52 , 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate a high prevalence of virulence factors among the studied isolates [ 23 ]. conducted a study on the virulence profile of P. mirabilis strains isolated from patients with UTI and found that 100% of the strains were positive for the mrpA , pmfA, and hmpA genes, whereas the zapA , ptA, and ucaA genes were found in 98.2%, 95.5%, and 95.5% of the strains, respectively [ 15 ]. also found high rates in their research: 98.4% of the strains were positive for the hpmA and atfA genes, and 92.1%, for the mrpA gene.…”
Section: Discussionmentioning
confidence: 99%